Extracellular calreticulin is present in the joints of patients with rheumatoid arthritis and inhibits FasL (CD95L)-mediated apoptosis of T cells. - Tarr, J; Winyard, P; Ryan, B; Harries, L; Haigh, R; Viner, N; Eggleton, P (2010)
OBJECTIVE: The binding of FasL (CD95L) to its receptor, Fas (CD95), induces apoptosis. Studies have shown that in patients with rheumatoid arthritis (RA), T lymphocytes are resistant to FasL-induced apoptosis in vivo but are susceptible to FasL-induced apoptosis in vitro. Dysfunction in this mechanism may be an important contributor to the pathophysiology of RA. Thus, the present study was undertaken to determine which factors might inhibit FasL-Fas binding in vivo and those that would inhibit apoptosis of T lymphocytes in an in vitro model system. METHODS: Human Jurkat T cells rendered apoptotic by FasL exposure were analyzed by flow cytometry. Necrosis was determined according to measurement of lactate dehydrogenase release. Quantification of calreticulin in plasma and synovial fluid and of calreticulin-FasL binding was performed by enzyme-linked immunosorbent assay. Measurement of nitrite/nitrate in the plasma and synovial fluid was carried out by chemiluminescence assay. RESULTS: Extracellular calreticulin was present at a significantly higher concentration in the plasma (median 10.3 ng/ml, interquartile range [IQR] 14.8 ng/ml) and synovial fluid (median 10.3 ng/ml, IQR 12.0 ng/ml) of RA patients (each P < 0.05) compared with the plasma (median 3.1 ng/ml, IQR 1.3 ng/ml) and synovial fluid (median 2.9 ng/ml, IQR 0.9 ng/ml) of patients with psoriatic arthritis and the plasma of healthy control subjects (median 2.9 ng/ml, IQR 0.9 ng/ml). Calreticulin concentrations in the synovial fluid correlated with the tender and swollen joint counts and the activity scores on the 28-joint Disease Activity Score assessment. Calreticulin also bound directly to FasL. In vitro, calreticulin (2-16 ng/ml) inhibited FasL-induced apoptosis of Jurkat T cells. CONCLUSION: Calreticulin was present at higher concentrations in the plasma and synovial fluid of RA patients. Calreticulin had the capacity to bind directly to FasL and to inhibit FasL-mediated apoptosis of Jurkat T cells, and thus might play a role in inhibiting apoptosis of inflammatory T cells in RA.